PENERAPAN MULTIMEDIA BASED LEARNING (MBL) PADA MATA PELAJARAN KIMIA UNTUK MENINGKATKAN SELF-REGULATED LEARNING (SRL) SISWA SMA N 1 SLEMAN (Jurnal Inovasi Pendidikan Kimia, 2020)
In the chemistry teaching and learning, Self-Regulated Learning (SRL) plays an important role in students’ academic motivation and also academic achievement. An innovation in chemistry teaching and learning, such as applying of Multimedia Based Learning (MBL), could increase the students’ SRL. The aims of this research were (1) to determine whether there is a difference SRL of high school students who applying MBL in chemistry teaching learning and students does not apply to the MBL, and (2) to determine whether there is an increased SRL high school students before and after applying MBL in chemistry teaching learning. The experiment was conducted in class XI SMA 1 Sleman to take Thermochemical matter. Researchers create a medium for these materials and continued with expert judgment of the media. Data SRL students were measured using validated questionnaires. Data analysis was performed using SPSS. The results showed that (1) there was no significant difference in SRL of students who participating in chemistry teaching learning by applying MBL and student who does not, which showed that the probability value of 0.711 or probability value 0.05; (2) there are significant differences in SRL of students before and after participating in chemistry teaching learning which applying MBL, which is seen from the results of paired samples t-test, the price of p (0,000) 0.05.